The Influence of Signaling Conspecific and Heterospecific Neighbors on Eavesdropper Pressure - Trillo, Paula A.; Benson, Christopher S.; Caldwell, Michael S.; Lam, Tiffany L.; Pickering, Oliver H.; Logue, David M. (Frontiers in Ecology and Evolution, 2019)
The study of tradeoffs between the attraction of mates and the attraction of eavesdropping predators and parasites has generally focused on a single species of prey, signaling in isolation. In nature however, animals often signal from mixed-species aggregations, where interactions with heterospecific group members may be an important mechanism modulating tradeoffs between sexual and natural selection, and thus driving signal evolution. Although studies have shown that conspecific signalers can influence eavesdropper pressure on mating signals, the effects of signaling heterospecifics on eavesdropper pressure, and on the balance between natural and sexual selection, are likely to be different. Here, we review the role of neighboring signalers in mediating changes in eavesdropper pressure, and present a simple model that explores how selection imposed by eavesdropping enemies varies as a function of a signaling aggregation’s species composition, the attractiveness of aggregation members to eavesdroppers, and the eavesdroppers’ preferences to attack different member types. This approach can be used to model mixed-species signaling aggregations, as well as same-species aggregations, including those with non-signaling individuals, such as satellites or females. We discuss the implications of our model for the evolution of signal structure, signaling behavior, mixed-species aggregations, and community dynamics.